Participatory Training Model in Improving Scientific Writing Competency - Rohimat, Japar; Kamil, Mustofa; Saripah, Iip (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This study aims to develop and evaluate a participatory training model for improving writing skills. Scientific writing skills are very important for educators, students, and professionals, not only as an academic task but also as a tool to develop critical, analytical, and creative thinking skills. Participatory training was designed systematically using the Research and Development (R&D) method, which includes literature review, product design, field testing, and revision, and involved 43 teachers selected by purposive sampling. The study results showed that this training significantly improved the scientific writing skills of teachers (H1), and the developed model was proven valid and effective (H2). Data analysis using the rating method, SPSS, and triangulation to ensure data credibility supported these findings. This training successfully overcomes obstacles in writing scientific papers, with strategic steps such as needs analysis, curriculum development, and constructive feedback. Interactive activities such as group discussions improve participants' understanding and skills. Positive responses from participants indicate increased motivation and competence, which confirms the importance of a participatory approach in professional development. These findings underline the importance of reflection in learning, which improves the quality of scientific publications among teachers.